Global food projections to 2020: emerging trends and alternative futures - Rosegrant, Mark W.; Paisner, Michael S.; Meijer, Siet; Witcover, Julie (International Food Policy Research Institute, 2001)
Over the years, it has become more and more apparent that any meaningful discussion of policies and priorities for alleviating malnutrition and poverty and achieving economic growth depends on an accurate assessment of where we have been and where we are headed. But forecasting the future of food supply and demand requires more than just an examination of short-term trends in global markets: it is essential to focus on long-term growth in income, population, agricultural technology, and a host of other pressing potential changes. IFPRI presented the first projections of global food supply and demand based on its IMPACT model in 1995 at its Washington, D.C., conference on a 2020 Vision for Food, Agriculture, and the Environment. The 2020 discussion paper that presented those first projections stressed that the prospects for global food security greatly depend not only on population growth and economic development but also on emerging issues such as trade liberalization, urbanization, environmental degradation, water scarcity, the livestock revolution, and new technologies. Two years later, IFPRI updated its take on the global food situation, extending its baseline scenario forward, and in 1999 further updated it, adding commodities and again extending the baseline. Now, in 2001, on the eve of another 2020 conference—”Sustainable Food Security for All”—to be held September 2001 in Bonn, Germany, IFPRI has once again fine-tuned its IMPACT model. In this volume, which reports the results of IFPRI’s projection work in far more detail than previous publications, the authors give their best assessment of what the future food situation will be in the baseline scenario. Then they examine the effects of changes in policy, technology, and life styles through two sets of alternative scenarios.